2010
DOI: 10.1080/09638180902989368
|View full text |Cite
|
Sign up to set email alerts
|

Is European Accounting Research Fairly Reflected in Academic Journals? An Investigation of Possible Non-mainstream and Language Barrier Biases

Abstract: Recent research has revealed that most articles published in top US accounting journals come from institutions based in the USA or a small number of other English-speaking countries (Jones and Roberts, Journal of Business Finance and Accounting, 32(5/6), pp. 1107-1140, 2005). It has also been shown that the research paradigm favoured by US journals is financial economics, with the result that articles on accounting history or social and behavioural accounting are very scarce. European journals exhibit a more d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 40 publications
0
23
0
2
Order By: Relevance
“…with its attendant methodology of positivism, while non-US journals have more diverse content and methodological heterogeneity (Raffournier and Schatt, 2010).…”
Section: Framework (Ref)mentioning
confidence: 99%
“…with its attendant methodology of positivism, while non-US journals have more diverse content and methodological heterogeneity (Raffournier and Schatt, 2010).…”
Section: Framework (Ref)mentioning
confidence: 99%
“…A maioria das publicações relevantes em contabilidade gerencial na Europa provém de pesquisadores que trabalham no Reino Unido (CARMONA; GUTIERREZ;CAMARA, 1999;JONES;ROBERTS, 2005;RAFFOURNIER;SCHATT, 2010). Particularmente, o que acontece no Reino Unido em termos de contabilidade gerencial é de certa forma diferente do que acontece no resto da Europa.…”
Section: Tendênciasunclassified
“…It is in this respect that Raffournier and Schatt (2010) argue that most accounting research published in top US accounting journals come from US institutions and that "non-English speaking scholars are at a competitive disadvantage in the race for publication in recognized periodicals" (p.1). Likewise, Borghans and Cörvers (2009) maintain that the Americanisation of European education is clearly seen in the change of language used in research from the national language German or French to English.…”
Section: English -The Dominant Languagementioning
confidence: 99%
“…Likewise, Raffournier and Schatt (2010) argue that "the top accounting research journals do not fairly reflect the variety of research conducted throughout the world because the number of research fields and methodologies is largely limited to financial accounting research using a positivist perspective and statistical methods, particularly in U.S. accounting research journals [which] clearly show that top US journals focus on a limited number of domains, methodologies and data origins" [Lukka and Kasanen, 1996;Bonner et al, (2006), p.11]. Similarly, Williams et al (2006) found that accounting research was dominated "by graduates of an elite set of schools who have demonstrated agility in employing the methods of economics and monetarist finance" (p.814).…”
Section: The Colonisation Of Accounting Researchmentioning
confidence: 99%
See 1 more Smart Citation